Isolation and identification of metabolites from the gram-negative Proteobacteria of Burkholderia cenocepacia and Serratia marcescens - Yap, Ann-Chee; Chan, Kok-Gan; Choo, Yeun-Mun (Penerbit Universiti Kebangsaan Malaysia, 2016)
Burkholderia cenocepacia and Serratia marcescens are Gram-negative proteobacteria commonly found in the natural environment and are also opportunistic pathogens that caused a number of human diseases. The fermentation culture of Burkholderia cenocepacia yielded three compounds, 4-(2-hydroxyethoxy)-phenol (1), Maculosin (2) and methyl myristate (3). Compound 2 was also isolated together with cyclo(L-Leu-L-Pro) (4) from Serratia marcescens. Compound 1 was isolated from a natural source for the first time and the first isolation of compounds 2-4 was also reported from both Burkholderia cenocepacia and Serratia marcescens.